Current prospects of building-integrated solar PV systems and the application of bifacial PVs - Abojela, Zuher R. Khalifa; Desa, Mohd Khairunaz Mat; Sabry, Ahmad H. (Frontiers in Energy Research, 2023)
Building-integrated solar photovoltaic (BIPV) systems have gained attention in current years as a way to recover the building’s thermal comfort and generate sustainable energy in building structures. BIPV systems can provide shade against sunshine while generating ancillary electrical power. Over the last decades, engineers have been trying to improve the efficiency of BIPV systems. BIPV systems with various installation types, including rooftop, balcony, curtain, sunshade, and wall façade types, are being constantly researched and intensively presented for improving power efficiency and reducing air-conditioning use. This work provides an overview of solar BIPV systems and focuses particularly on existing applications of the bifacial type of BIPV systems. The motivation and an overview of BIPV systems are first introduced, followed by the study methodology considered and the contributions. This work discusses PV technologies of bifacial PVs (monocrystalline and polycrystalline bifacial modules), BIPV installation [curtains, rooftop, flat rooftop, transparent faced, balcony windows (transparent), wall opaque facade, flat roof-faced, and skylight sunshade types], simulation and optimization software (simulation software and future trends), zero-energy BIPV technology, and optimization techniques of BIPV systems. Last, suggestion amendments to the current BIPV design that possibly contribute to growing the system’s effectiveness, reliability, and cost as future design theories for the whole system are presented.